2019
DOI: 10.12688/f1000research.20183.1
|View full text |Cite
|
Sign up to set email alerts
|

Stage 1 Registered Report: How subtle linguistic cues prevent unethical behaviors

Abstract: Different ways of description can easily influence people’s evaluation and behaviors. A previous study suggested that subtle linguistic differences in ethical reminder instructions can cause differences in preventing readers’ unethical behavior. The present study aims to replicate the previous finding by Bryan and his colleagues (2013) in the Japanese context, additionally exploring the influence of unfamiliar instructions that capture participants’ attention. In two experiments, which are planned to be conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Crowdsourcing. The protocol of this experiment was registered on the Open Science Framework (Guo et al, 2020). The results showed that the familiarity rating score in the "cheater" condition was significantly lower than that in the "cheating" condition, t(64) = 6.73, p < .001, Cohen's d = 0.834.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crowdsourcing. The protocol of this experiment was registered on the Open Science Framework (Guo et al, 2020). The results showed that the familiarity rating score in the "cheater" condition was significantly lower than that in the "cheating" condition, t(64) = 6.73, p < .001, Cohen's d = 0.834.…”
Section: Methodsmentioning
confidence: 99%
“…Underlying data Open Science Framework: How subtle linguistic cues prevent unethical behaviors, https://doi.org/10.17605/OSF.IO/AXDHV (Guo et al, 2020).…”
Section: Data Availabilitymentioning
confidence: 99%
“…Sedangkan dalam penelitian Chernov (2018) menyebutkan bahwa: "Priming refers to the effect of some preceding stimulus or event on how we react, broadly defined, to some subsequent event or person-Priming mengacu pada efek pemberian beberapa stimulus atau peristiwa sebelumnya terhadap reaksi seseorang pada suatu peristiwa tertentu setelahnya " Dari definisi tersebut, seringkali efek priming dianggap sebagai hasil dari aktivasi dari representasi mental yang dapat meningkatkan atau mengurangi perilaku nampak selanjutnya sesuai dengan peristiwa tertentu (Rivers & Sherman, 2018). Para psikolog sosial melakukan adaptasi terkait metodologi priming untuk memahami bagaimana aktivasi pengetahuan dan evaluasi dapat memengaruhi persepsi dan perilaku indiividu, khususnya dalam penelitian eksperimental, guna pencegahan perilaku curang (Bryan, Adams & Monin, 2013;Guo, et. al., 2019).…”
Section: "Priming Refers To the Incidental Influence Of Environmental...unclassified